FOTOSENSITIVITY IN CHILDREN AND ADOLESCENTS, ESPECIALLY THE COURSE AND TACTICS - I. O. Shchederkina; V. A. Karlov (Эпилепсия и пароксизмальные состояния)
Fotoparoxismal reaction (FPR) on the EEG is often on receiving child neurologist, epileptologist. It is registered as patients with epilepsy (not just fotosensitivety) and in patients without epileptic seizures. The results of observations of two groups of children with fotoparoxismal reaction in the EEG: 44 children with no history of epileptic seizures and 116 – with various forms of epilepsy. Children with IDF without this type of epileptic seizures abnormal activity in the EEG was most often monosymptomatic or combined with spontaneous generalized epileptiform activity in the background and during hyperventilation. Children diagnosed with epilepsy and a third of the IDF had a combination of different attacks, dominated by generalized tonic-clonic, myoclonic, and complex partial absense. Should be video-EEG monitoring of sleep day or night to the additional tests to rule out “subclinical” seizures in children with known IDF on a routine EEG. Children without epileptic seizures with the IDF is not recommended antiepileptic therapy before the appearance of epileptic seizures.